The living experience of surviving out‐of‐hospital cardiac arrest and spiritual meaning making - Maria Aristidou; Maria Karanikola; Elizabeth Kusi‐Appiah; Anna Koutroubas; Usha Pant; Foteini Vouzavali; Ekaterini Lambrinou; Elizabeth Papathanassoglou (Wiley, 2023)
Abstract Aim To understand the meaning of surviving out of hospital cardiac arrest and its aftereffects among Greek‐speaking survivors. Design Hermeneutical phenomenological method based on Martin Heidegger's philosophy. Methods Eight Greek‐speaking out of hospital cardiac arrest survivors were recruited using purposive sampling method. Data collection and analysis using the seven stages of hermeneutic analysis described by Diekelman. Data were collected through semi‐structured personal interviews with open‐ended questions. Results Analysis revealed five themes: 'The unexpected attack', 'Experiencing a different world: Transformation of Body, Time, Emotion and Sensation', 'Restoration of the re‐embodied self', 'Life transformation' and 'Personal transformation'. The themes are commensurate with transcultural components of Near‐Death Experiences. Surviving out of hospital cardiac arrest was perceived as a 'divine gift' and a chance to continue 'living in a more conscious and meaningful way'. Despite participants' physical and psychosocial challenges, the narratives highlighted a newly acquired deep appreciation for the joy of life, living and others. Construction of meaning and a heightened spirituality seem central in reconstructing life after out of hospital cardiac arrest survivors. Patient or Public Contribution Out of hospital cardiac arrest survivors reflected and described in‐depth on their lived experiences of out of hospital cardiac arrest through a 60‐ to 90‐min interview. In addition, the participants provided their feedback on the interpretation of the findings, confirmed the study findings, and ensured that the analysis reflected aspects of their individual experiences and were true to them.